DILEMA PRODUK TEMBAKAU DI ERA GLOBALISASI: STUDI KOMPARATIF ROKOK INDONESIA DALAM LINGKUP ASEAN - Rosyid, M.; Hanny, O. (Fakultas Pertanian UGM, 2017)
Tobacco products have always been controversial in the context of goverment revenues versus health costs. This study aims to analyze the demand for cigarettes and other aspects that related to cigarette consumption in Indonesia. The research approach is a comparative descriptive study of Indonesia with some ASEAN countries (Brunei, Cambodia, Laos, Malaysia, Philippines, Singapore, Thailand and Vietnam). The variables or aspects analyzed include: Smoking Prevalence, Price Level, Percentage of Excise and Tax Receipts from cigarettes. Other aspects analyzed include the estimated health costs of cigarettes and the ratio of cigarette costs to tax revenues. The results of the empirical studies show that within ASEAN, the prevalence rate of smoking for Indonesian adult men is the highest. More than half of adult males in Indonesia are active smokers. Meanwhile, almost all adult smoking prevalence in other countries in the ASEAN region is well below 50%. The relatively cheap price of cigarettes can be an indication of the high prevalence of smoking in Indonesia.